Arc and Slab-Failure Magmatism in Cordilleran Batholiths I: The Cretaceous Coastal Batholith of Peru and its Role in South American Orogenesis and Hemispheric Subduction Flip - Hildebrand, Robert; Whalen, Joseph (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
We examined the temporal and spatial relations of rock units within the Western Cordillera of Peru where two Cretaceous basins, the Huarmey-Cañete and the West Peruvian Trough, were considered by previous workers to represent western and eastern parts respectively of the same marginal basin. The Huarmey-Cañete Trough, which sits on Mesoproterozoic basement of the Arequipa block, was filled with up to 9 km of Tithonian to Albian tholeiitic–calc-alkaline volcanic and volcaniclastic rocks. It shoaled to subaerial eastward. At 105–101 Ma the rocks were tightly folded and intruded during and just after the deformation by a suite of 103 ± 2 Ma mafic intrusions, and later in the interval 94–82 Ma by probable subduction-related plutons of the Coastal batholith. The West Peruvian Trough, which sits on Paleozoic metamorphic basement, comprised a west-facing siliciclasticcarbonate platform and adjacent basin filled with up to 5 km of sandstone, shale, marl and thinly bedded limestone deposited continuously throughout the Cretaceous. Rocks of the West Peruvian Trough were detached from their basement, folded and thrust eastward during the Late Cretaceous–Early Tertiary. Because the facies and facing directions of the two basins are incompatible, and their development and subjacent basements also distinct, the two basins could not have developed adjacent to one another. Based on thickness, composition and magmatic style, we interpret the magmatism of the Huarmey- Cañete Trough to represent a magmatic arc that shut down at about 105 Ma when the arc collided with an unknown terrane. We relate subsequent magmatism of the early 103 ± 2 Ma syntectonic mafic intrusions and dyke swarms to slab failure. The Huarmey- Cañete-Coastal batholithic block and its Mesoproterozoic basement remained offshore until 77 ± 5 Ma when it collided with, and was emplaced upon, the partially subducted western margin of South America to form the east-vergent Marañon fold–thrust belt. A major pulse of 73–62 Ma plutonism and dyke emplacement followed terminal collision and is interpreted to have been related to slab failure of the west-dipping South American lithosphere. Magmatism, 53 Ma and younger, followed terminal collision and was generated by eastward subduction of Pacific oceanic lithosphere beneath South America. Similar spatial and temporal relations exist over the length of both Americas and represent the terminal collision of an arc-bearing ribbon continent with the Americas during the Late Cretaceous–Early Tertiary Laramide event. It thus separated longstanding westward subduction from the younger period of eastward subduction characteristic of today. We speculate that the Cordilleran Ribbon Continent formed during the Mesozoic over a major zone of downwelling between Tuzo and Jason along the boundary of Panthalassic and Pacific oceanic plates.